Penggunaan Model ICARE dengan Media Make and Match untuk Meningkatkan Hasil Belajar pada Pelajaran PAI - Hasyim, Muhammad (JURNAL PUSAKA, 2023)
Model ICARE is a framework that is used as a guideline in carrying out learning activities. To improve the learning outcomes as desired, the researcher applies Make and Match media as supporting model to improve student learning outcomes. Make and Match media itself is a learning media that prioritizes the cultivation of social skills, especially the ability to work in team, interact with people, and the ability to think fast and critical through the game of finding a partner with the help of cards. After implementing the model ICARE with Make and Match Media, students improved their learning skill. In the pre-action learning activities, the number of students who got a score above the KKM was 2 students or 6.7% with a score of 80. In the first cycle of action the number of students who completed it was 13 students or 43.3% with a score of 80. And in the second cycle of action the number of students who got a score above the KKM totaling 30 students or 100% with a score of 80 as many as 21 students or 70%, 6 students got a score of 90 or 20% and students who got a score of 100 were 3 students or 10%.